Activity of the trunk and leg musculature during the flutter kick - Kaneoka, K.; Imai, A.; Kohdate, M. (Sports Performance, 2015)
There are no in-depth biomechanical studies about swimming because detailed analyses of motion and muscle activity in water are difficult. In the present study, we measured the activity of trunk and leg muscles during the flutter kick, using a waterproof, wireless electromyographic system. Flutter kick movements were recorded by a waterproof high-speed camera, and were divided into four phases to analyze muscle activity in each phase: (1) hip extension-knee extension, (2) hip extension-knee flexion, (3) hip flexion-knee flexion, and (4) hip flexion-knee extension. The femoral biceps and gastrocnemius became active from Phase 1 to 2, the rectus femoris and vastus medialis became active from Phase 3 to 4, and the internal oblique muscle activity was high from Phase 2 to 3. In this study, the muscle activity patterns during the flutter kick were described. It was suggested that for this kick the internal oblique muscle has an important role during the switch over from hip extension to flexion.